Pelvic fin walking and punting behaviour of Raja radula Delaroche, 1809 observed in the Sea of Marmara - BILECENOGLU, M.; EKSTROM, L. J. (Mediterranean Marine Science, 2013)
A mature female rough ray (Raja radula Delaroche, 1809) individual was observed at Sea of Marmara during a scuba dive to perform pelvic fin walking and punting, which was a previously unrecorded rajid behaviour from the Mediterranean Sea. The underwater video footage were analyzed, in which the average distance travelled per punt was measured as 0.40 disc length (DL) at an average speed of 0.26DL per second.